Ho Chi Minh's Educational Philosophy: A Framework for Cultivating National Identity and Global Citizenship - Nguyen Hoang Long; Tran Thi Thu Thao (PT. Berkah Smart Academica, 2026)
This study aims to explore Ho Chi Minh's educational philosophy as a strategic framework for balancing the strengthening of national identity and the cultivation of global citizenship awareness in Vietnam. Amidst the currents of globalization and digital transformation, the Vietnamese education system faces challenges in preserving local values while integrating international competency standards. Using a qualitative method through a Systematic Literature Review (SLR) from Scopus databases, this study analyzes the integration of